(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The objectives were to determine the appropriate level of dried cassava top (DCT) in total mixed ration (TMR) based on production performance and carcass characteristics of fattening Charolais crossbred steers. Materials and Methods: Fifteen fattening Charolais crossbred steers were randomly assigned to a randomized complete block design with initial body weight to receive three treatments, including without DCT, 15% DCT, and 30% DCT in TMR, on a dry matter (DM) basis. The production trial lasted 120 days; then, the fattened steers were slaughtered to study the carcass characteristics. Results: The in vitro gas production from the immediately soluble fraction of TMR containing 30% DCT was higher than the others (p < 0.05). However, in vitro DM and organic matter degradability were not significantly different among treatments. Feed intake, final weight, feed cost per gain, and carcass characteristics such as warm carcass percentage, marbling score, and loin eye area of feedlot steers were not affected by the inclusion of DCT in TMR. Although steers fed TMR containing 15% DCT had body weight gain, average daily gain, and feed conversion ratio lower than the control (p < 0.05); however, the use of DCT at 30% DM in TMR reduced the feed cost of feedlot beef production (p < 0.05). Conclusion: Using local ingredients such as cassava tops can increase profit margins for farmers without sacrificing product quality, but they must closely look at growth performance. J. Adv. Vet. Anim. Res., 10(3): 507–515, September 2023 http://doi.org/10.5455/javar.2023.j704